The Impact of Virtual Technology on Teachers Candidates’ Self-efficacy: A Literature Revie - Sadia Bibi (International Islamic University Islamabad, 2020)
This study evaluated the impact of virtual technology on teacher candidates’ self-efficacy. Teacher self-efficacy based on empirical validity in face-to-face environments remains continuously, while it is a new concept in an online education environment. The following literature review conducted among different academic electronic databases and examined the 15 years passed published work. The literature review explores three major areas of research in online education about technology on teacher candidates’ self-efficacy. (1) self-efficacy of pre-service teachers by adopting virtual technology (2) association between teaching self-efficacy and virtual technology (3) changes in self-efficacy of a teacher before and after a professional development with the help of virtual technology. The study described that different researchers continuously examine the balance between pedagogical and technological knowledge that supports the professional development of pre-service teacher self- efficacy with the help of virtual technology, whether teacher self-efficacy differs in online education as compared to face-to-face education.